Improving Hyperactive Student Learning Behavior in Teaching Learning Activities Using Self-Counseling Method in Class VII-B SMPN 3 Surabaya - Sanawiyah, Siti (Indonesian Journal of Contemporary Education, 2019)
Students who exhibit hyperactive behavior can be at high risk such as failing at school, experiencing serious social problems, including difficulty getting along as well as conflict with family members, being hated by siblings, often scolded and punished by caregivers. All of these factors can have an impact on students' social lives and influence the emergence of chaos in student attitudes and behavior. Indicators of student hyperactivity include: 1) difficulty focusing, 2) often not doing assignments, 3) unable to sit quietly, 4) often flicking friends, 5) impulsive, 6) often monopolizing activities in social interaction. The impact of students' hyperactive behavior is: 1) decreased learning achievement, 2) lack of harmony in social relations with peers. Hyperactive behavior is influenced by the pattern of parental care that is authoritarian and unattended. This research aims to improve the behavior of hyperactive students in teaching and learning activities in SMP Negeri 3 Surabaya with the method of self-counseling. The type of research used is qualitative research in the form of case studies of students who behave hyperactively. The techniques used in collecting data are interviews, observation, and documentation analysis. The data obtained were analyzed by qualitative descriptive analysis. The results showed that hyperactive student behavior can be improved by using the self-counseling method in teaching and learning activities. This is indicated by an increase in the activity of students in the first cycle of students who are active at 85.71% and in cycle 2 by 100%. from the initial value (62%) then cycle 1 (75%) and cycle 2 (85%). The action of the first cycle grade average value increased to 79.18 (completeness 52.6%), in the second cycle increased again to 87.87 (completeness 86.8%).